2007
DOI: 10.1111/j.1475-097x.2007.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure response to isometric exercise in patients with peripheral atherosclerotic disease

Abstract: Our study indicates that the pressor response continues to be well regulated with age, also when the cardiovascular system is altered by marked atherosclerosis. The consequence is that both PAD patients and elderly controls reach higher SP values during isometric exercise due to higher SP baseline values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 55 publications
4
26
0
1
Order By: Relevance
“…Indeed, we found that coronary hyperemia is also impaired in PAD during isometric handgrip exercise. While CBV responses to handgrip were attenuated in PAD, the increase in BP and HR were similar to healthy subjects, which is consistent with other studies [16]. The pressor response generated during plantar flexion exercise is greater in PAD.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, we found that coronary hyperemia is also impaired in PAD during isometric handgrip exercise. While CBV responses to handgrip were attenuated in PAD, the increase in BP and HR were similar to healthy subjects, which is consistent with other studies [16]. The pressor response generated during plantar flexion exercise is greater in PAD.…”
Section: Discussionsupporting
confidence: 91%
“…Bakke EF et al, [19] also showed a increase in the mean arterial pressure, which was consistent with our study results. An increased total peripheral resistance was the main factor which caused an increase in the blood pressure.…”
Section: Discussionsupporting
confidence: 83%
“…Cardiovascular responses during walking are altered in patients with PAD(3, 5). Previous studies have reported that blood pressure (BP) and heart rate (HR) both increase during constant load exercise in patients with PAD, but not in age matched controls(5).…”
Section: Introductionmentioning
confidence: 99%